2007
DOI: 10.1017/s0033291707000189
|View full text |Cite
|
Sign up to set email alerts
|

Puberty moderates genetic influences on disordered eating

Abstract: These findings suggest that puberty influences the expression of genes for disordered eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
103
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 37 publications
17
103
0
Order By: Relevance
“…Puberty has been a primary focus of this research, as puberty occurs between pre-to mid-adolescence, puberty is related to a cascade of biological and psychosocial transitions, and puberty is associated with increases in the incidence of disordered eating in females (Bulik 2002;Graber et al 1994). Developmental twin studies have confirmed that puberty increases or "moderates" the heritability of disordered eating symptoms, even after controlling for age (Culbert et al 2009;Klump et al 2003;Klump et al 2007b). Little-to-no genetic influences on disordered eating were found in prepubertal 11-year-old twins, whereas genetic effects accounted for approximately 50% of the variance in 11-year-old twins who were in mid-to late puberty (Klump et al 2003).…”
Section: Puberty and The Heritability Of Disordered Eating Symptomsmentioning
confidence: 99%
“…Puberty has been a primary focus of this research, as puberty occurs between pre-to mid-adolescence, puberty is related to a cascade of biological and psychosocial transitions, and puberty is associated with increases in the incidence of disordered eating in females (Bulik 2002;Graber et al 1994). Developmental twin studies have confirmed that puberty increases or "moderates" the heritability of disordered eating symptoms, even after controlling for age (Culbert et al 2009;Klump et al 2003;Klump et al 2007b). Little-to-no genetic influences on disordered eating were found in prepubertal 11-year-old twins, whereas genetic effects accounted for approximately 50% of the variance in 11-year-old twins who were in mid-to late puberty (Klump et al 2003).…”
Section: Puberty and The Heritability Of Disordered Eating Symptomsmentioning
confidence: 99%
“…Few studies that have assessed whether subjects with early vs later onset of a disorder vary in terms of the influence of genetics on the risk of becoming eating disordered. [28][29][30] More research is needed to better understand these associations.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Few studies that have assessed whether subjects with early vs later onset of a disorder vary in terms of the influence of genetics on the risk of becoming eating disordered. [28][29][30] More research is needed to better understand these associations.Although teasing or negative comments about weight have been proposed as risk factors for becoming eating disordered, the evidence is mixed. Haines et al 10 found that the females in Project EAT (Eating Among Teens) who were teased were more likely to become frequent dieters 5 years later, but they did not observe an association between teasing and the development of bulimic behavior.…”
mentioning
confidence: 99%
“…Genetic and environmental contributions to the variance in DE at age 11 years (which are represented as a 11 , c 11, and e 11 in the figure) are obtained by simply squaring their respective path estimates. The genetic and environmental variance in DE at age 14 years is decomposed into components attributable to the genetic and environmental effects on DE at age 11 years (represented as the square of a 21, c 21, e 21 ) as well as residual components that are independent of the genetic and environmental variance at age 11 years (represented as the square of a 22 , c 22, e 22, ).…”
Section: Statistical Analysesmentioning
confidence: 99%